2020
DOI: 10.1177/1359105320962242
|View full text |Cite
|
Sign up to set email alerts
|

The centrality of disclosure decisions to the illness experience for youth with chronic conditions: A qualitative study

Abstract: The aim of this paper is to illuminate findings of disclosure experiences for youth living with chronic illness using a non-categorical approach. The findings were derived from a larger qualitative study framed by social constructivist grounded theory that sought to understand youth’s involvement in healthcare decision-making in the context of chronic illness. Fifty-four youth participated in the study, ranging from 9 to 24 years. Three main themes representing the youth’s perspectives and experiences of discl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(37 citation statements)
references
References 51 publications
(66 reference statements)
2
35
0
Order By: Relevance
“…A qualitative interview of young patients with chronic conditions showed that their illness experience was complex and intense and they needed active support [13], which is consistent with our conclusion. For example, they wanted to be noticed and listened to when expressing their feelings, and they wanted to seek more care instead of being ignored [13]. Our results showed that young and middle-aged SSNHL patients had a variety of symptoms at the onset and wanted more care and attention as well.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A qualitative interview of young patients with chronic conditions showed that their illness experience was complex and intense and they needed active support [13], which is consistent with our conclusion. For example, they wanted to be noticed and listened to when expressing their feelings, and they wanted to seek more care instead of being ignored [13]. Our results showed that young and middle-aged SSNHL patients had a variety of symptoms at the onset and wanted more care and attention as well.…”
Section: Discussionsupporting
confidence: 90%
“…Psychology, drug toxicity, rest and sleep, and noise in the environment may affect the onset of SSNHL symptoms [12]. A qualitative interview of young patients with chronic conditions showed that their illness experience was complex and intense and they needed active support [13], which is consistent with our conclusion. For example, they wanted to be noticed and listened to when expressing their feelings, and they wanted to seek more care instead of being ignored [13].…”
Section: Discussionsupporting
confidence: 88%
“…Although disclosure was used in some cases to obtain social support, others avoided disclosing their illness to minimize impacts on social relationships and employment. Unfortunately, concealment of a chronic illness exacerbates stress and psychological distress, creating somewhat of a catch‐22 situation for many patients 37–41 . One participant reported sometimes blaming symptoms on food poisoning instead of gastroparesis, an explanation which would be temporary and therefore less stigmatized than chronic illness.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, concealment of a chronic illness exacerbates stress and psychological distress, creating somewhat of a catch-22 situation for many patients. [37][38][39][40][41] One participant reported sometimes blaming symptoms on food poisoning instead of gastroparesis, an explanation which would be temporary and therefore less stigmatized than chronic illness. Several cited concerns about how their illness would be perceived by supervisors at work and two participants noted direct, negative impacts on their employment, including being laid off and missing opportunities for advancement due to their illness.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, there has been limited research to inform our understanding of 'what' it is that children understand about their illness, the way a young child makes decisions about 'who' they share information about their illness with, and 'how' they share that information with (Bray et al, 2015(Bray et al, , 2022Carter et al, 2017). Existing studies tend to take the perspective of older children (Lambert and Keogh, 2015;Woodgate et al, 2022). However, this study offers a nuanced and close examination of the experiences of young children living with a long-term condition across three countries, providing rich insights into key elements of health literacy from the perspective of the children themselves.…”
Section: Discussionmentioning
confidence: 99%